Pengembangan Media Komik Digital Berbasis Faktual pada Materi Pencemaran Lingkungan untuk Siswa Kelas X SMA: (The Development of Factual-Based Digital Comic Media on Environmental Pollution Materials for Class X High School) - Desi Wulansari; Asni Johari; Revis Asra (BIODIK, 2022)
This study aims to determine the feasibility and effectiveness of digital comic media on environmental pollution material for class X high school students, as well as students' perceptions of the media. This study uses the ADDIE model development design. The data collection technique used a questionnaire sheet and multiple choice questions. The instrument used was a validation questionnaire sheet to determine the feasibility of the media, teacher, and student-response questionnaires to determine the attractiveness of the media and multiple-choice questions to determine the effectiveness of the media. Data analysis techniques used in research and development are qualitative and quantitative. Based on the results of the validation of the development of digital comic media by material experts twice and media experts once the media was declared valid and could be tested, while the teacher response results obtained a percentage of 94% in the very good category, the results of student responses in small group trials obtained a percentage of 93 % in the very good category, the results of student responses in the large group trial obtained a percentage of 87% in the very good category and the results of field trials or effectiveness obtained a score of 54 in the control class and 71 in the experimental class, which means that learning outcomes using digital comic media are more effective. So it can be concluded that digital comics are feasible to be used as teaching materials. Key words: Development, Digital Comics, Environmental Pollution Â  Abstrak. Penelitian ini bertujuan untuk mengetahui kelayakan dan keefektifan media komik digital pada materi pencemaran lingkungan untuk siswa kelas X SMA, serta persepsi siswa terhadap media tersebut. Penelitian ini menggunakan desain pengembangan model ADDIE. Teknik pengumpulan data menggunakan lembar angket dan soal pilihan ganda. Instrument yang digunakan berupa lembar angket validasi untuk mengetahui kelayakan media, angket respon guru dan siswa untuk mengetahui kemenarikan media dan soal pilihan ganda untuk mengetahui efektifitas media. Teknik analisis data yang digunakan dalam penelitian dan pengembangan yaitu kualitatif dan kuantitatif. Berdasarkan hasil validasi terhadap pengembangan media komik digital oleh ahli materi sebanyak dua kali dan ahli media sebanyak satu kali media dinyatakan valid dan dapat diujicobakan, sedangkan hasil respon guru diperoleh persentase 94% dalam kategori sangat baik, hasil respon siswa dalam ujicoba kelompok kecil diperoleh persentase 93% dalam kategori sangat baik, hasil respon siswa dalam ujicoba kelompok besar diperoleh persentase 87% dalam kategori sangat baik dan hasil ujicoba lapangan atau efektifitas diperoleh skor 54 pada kelas kontrol dan 71 pada kelas eksperimen yang berarti hasil belajar dengan menggunakan media komik digital lebihÂ  efektif. Sehingga dapat disimpulkan bahwa komik digital layak untuk digunakan sebagai bahan ajar. Kata kunci: Pengembangan, Komik digital, Pencemaran lingkungan